Effects of aluminum foam filling on the low-velocity impact response of sandwich panels with corrugated cores. (May 2020) - Yan, LL; Yu, B; Han, B; Zhang, QC; Lu, TJ; Lu, BH
In this study, a closed-cell aluminum foam was filled into the interspaces of a sandwich panel with corrugated cores to form a composite structure. The novel structure is expected to have enhanced foam-filled cores with high specific strength and energy absorption capacity. An out-of-plane compressive load under low-velocity impact was experimentally and numerically carried out on both the empty and foam-filled sandwich panels as well as on the aluminum foam. It is found that the empty corrugated sandwich panel has poor energy absorption capacity due to the core member buckling compared to that of the aluminum foam. However, by the filling of the aluminum foam, the impact load resistance of the corrugated panel was increased dramatically. The loading-time response of the foam-filled panel performs a plateau region like the aluminum foam, which has been proved to be an excellent energy absorption material. Numerical results demonstrated that the aluminum foam filling can decrease the corrugated core member defects sensitivity and increase its stability dramatically. The plastic energy dissipation of the core member for the foam-filled panel is much higher than that of the empty one due to the reduced buckling wavelength caused by the aluminum foam filling.